Interaction of the neutral amino acid transporter ASCT2 with basic amino acids. Issue 8 (27th April 2020) - Ndaru, Elias; Garibsingh, Rachel-Ann A.; Zielewicz, Laura; Schlessinger, Avner; Grewer, Christof
Abstract : Glutamine transport across cell membranes is performed by a variety of transporters, including the alanine serine cysteine transporter 2 (ASCT2). The substrate-binding site of ASCT2 was proposed to be specific for small amino acids with neutral side chains, excluding basic substrates such as lysine. A series of competitive inhibitors of ASCT2 with low µM affinity were developed previously, on the basis of the 2, 4-diaminobutyric acid (DAB) scaffold with a potential positive charge in the side chain. Therefore, we tested whether basic amino acids with side chains shorter than lysine can interact with the ASCT2 binding site. Molecular docking of L-1, 3-diaminopropionic acid (L-DAP) and L-DAB suggested that these compounds bind to ASCT2. Consistent with this prediction, L-DAP and L-DAB, but not ornithine, lysine or D-DAP, elicited currents when applied to ASCT2-expressing cells. The currents were carried by anions and showed the hallmark properties of ASCT2 currents induced by transported substrates. The L-DAP response could be eliminated by a competitive ASCT2 inhibitor, suggesting that binding occurs at the substrate binding site. The K M for L-DAP was weakly voltage dependent. Furthermore, the pH dependence of the L-DAP response showed that the compound can bind in several protonation states. Together, these results suggest that the ASCT2 binding site is able to recognize L-amino acids with short, basic side chains, such as the L-DAP derivative β-N-methylamino-l -Alanine (BMAA), a well-studied neurotoxin. Our results expand the substrate specificity of ASCT2 to include amino acid substrates with positively charged side chains.